2009
DOI: 10.1103/physrevb.79.085413
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and chemical contributions to the stability of magnetic surface alloys on Ru(0001)

Abstract: We have used density functional theory to study the structural stability of surface alloys. Our systems consist of a single pseudomorphic layer of MxN1−x on the Ru(0001) surface, where M = Fe or Co, and N = Pt, Au, Ag, Cd, or Pb. Several of the combinations studied by us display a preference for atomically mixed configurations over phase-segregated forms. We have also performed further ab initio calculations to obtain the parameters describing the elastic interactions between atoms in the alloy layer, includin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…2) that some of these pairs (Co-Ag, Fe-Ag) do not quite mix on Rh(1 1 1) too. Our finding for Co-Ag is similar to the experimental finding by Thayer et al on Ru(0 0 0 1) [25] as well as corresponding first-principles calculations [24,25]. In the experiment they found that Ag and Co on Ru(0 0 0 1) do not show atomic-level mixing.…”
Section: Structure and Miscibility And The Effect Of Magnetismsupporting
confidence: 94%
See 2 more Smart Citations
“…2) that some of these pairs (Co-Ag, Fe-Ag) do not quite mix on Rh(1 1 1) too. Our finding for Co-Ag is similar to the experimental finding by Thayer et al on Ru(0 0 0 1) [25] as well as corresponding first-principles calculations [24,25]. In the experiment they found that Ag and Co on Ru(0 0 0 1) do not show atomic-level mixing.…”
Section: Structure and Miscibility And The Effect Of Magnetismsupporting
confidence: 94%
“…In earlier work, we have already reported on the mixing and some magnetic properties of two-dimensional magnetic surface alloys of the form M x N 1 À x on Ru(0 0 0 1) [24]. In this paper, we present results on the magnetic properties of similar surface alloys on a Rh(1 1 1) substrate.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…We have already reported a study of the mixing and magnetic properties of (i) systems of the type M x N 1Àx /S, where M is a magnetic element (Fe or Co), N is a non-magnetic element (Pt, Au, Ag, Cd or Pb), and S is Ru(0 0 0 1) [10], and (ii) Co-Ag on Rh(1 1 1) [11] and (iii) Ni-Pt on Rh(1 1 1) [12]. These studies were performed using ab initio density functional theory calculations.…”
Section: Introductionmentioning
confidence: 99%
“…We use the Morse and three-cosine potentials, parameterized for two-body (Co-Sb, Co-Co, Sb-Sb, and Ba-Sb) and three-body (Co-Sb-Sb) interactions [20,22,28]. Interatomic potentials are simplified fields and the CRs are approximations, therefore these potentials cannot accurately predict, for example, formation energy.…”
mentioning
confidence: 99%